2018
DOI: 10.1074/jbc.ra118.004220
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α elicits phenotypic and functional alterations of vascular smooth muscle cells by miR-155-5p–dependent down-regulation of cGMP-dependent kinase 1

Abstract: cGMP-dependent protein kinase 1 (PKG1) plays an important role in nitric oxide (NO)/cGMP-mediated maintenance of vascular smooth muscle cell (VSMC) phenotype and vasorelaxation. Inflammatory cytokines, including tumor necrosis factor-α (TNFα), have long been understood to mediate several inflammatory vascular diseases. However, the underlying mechanism of TNFα-dependent inflammatory vascular disease is unclear. Here, we found that TNFα treatment decreased PKG1 expression in cultured VSMCs, which correlated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 50 publications
2
36
0
Order By: Relevance
“…Furthermore, the elevated NOx levels in the patients were negatively correlated with eNOS mRNA levels and positively correlated with iNOS mRNA levels ( Figure 2 H,I), suggesting that the increased NO/cGMP levels in the patients might be derived from increased iNOS expression. Since inflammatory cytokines, including TNF-α, stimulate the iNOS/NO/cGMP pathway [ 26 ] and inhibit the eNOS/NO/cGMP pathway [ 15 , 16 , 17 , 18 , 19 ], the relationship between serum levels of TNF-α and eNOS or iNOS expression was assessed. Our results showed that the serum TNF-α levels were significantly increased in PE patients ( Figure 2 J) and positively correlated with the sFlt1/PlGF ratio ( Figure 2 K).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the elevated NOx levels in the patients were negatively correlated with eNOS mRNA levels and positively correlated with iNOS mRNA levels ( Figure 2 H,I), suggesting that the increased NO/cGMP levels in the patients might be derived from increased iNOS expression. Since inflammatory cytokines, including TNF-α, stimulate the iNOS/NO/cGMP pathway [ 26 ] and inhibit the eNOS/NO/cGMP pathway [ 15 , 16 , 17 , 18 , 19 ], the relationship between serum levels of TNF-α and eNOS or iNOS expression was assessed. Our results showed that the serum TNF-α levels were significantly increased in PE patients ( Figure 2 J) and positively correlated with the sFlt1/PlGF ratio ( Figure 2 K).…”
Section: Resultsmentioning
confidence: 99%
“…Our recent studies demonstrated that miRNA (miR)-31-5p and miR-155-5p are detected at high levels in sera from patients with PE. These miRNAs elicit vascular dysfunction associated with hypertension and proteinuria through the impairment of the endothelial nitric oxide synthase/nitric oxide (eNOS/NO) and soluble guanylate cyclase/protein kinase G (sGC/PKG) pathways [ 15 , 16 , 17 , 18 , 19 ]. This suggests that PE-derived miRNAs associated with the impairment of vasorelaxation and vascular remodeling can be used as diagnostic and therapeutic biomarkers of PE.…”
Section: Introductionmentioning
confidence: 99%
“…TNF-α is primarily produced by monocyte macrophage system in AAA [ 26 , 47 ]. Previous studies have revealed that TNF-α could induce VSMCs from contractile to synthetic phenotype through the downregulation of VSMC-specific contractile genes [ 48 , 49 ]. In this study, we demonstrated that UC-MSCs suppress TNF-α expression during AAA initiation and progression, which implies that UC-MSCs might promote the phenotypic transition of VSMCs through indirect pathways, such as downregulating the expression level of TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…PKG plays an important role in maintenance of vascular smooth muscle phenotype and vascular relaxation (Choi et al, 2018). Activation of PKG in VSMC can lead to phosphorylation of VASP at serine 239, resulting in vascular relaxation (Holt et al, 2016).…”
Section: Discussionmentioning
confidence: 99%